2022
DOI: 10.3390/ijms23052643
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions of Tannic Acid with Proteins Associated with SARS-CoV-2 Infectivity

Abstract: The overall impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on our society is unprecedented. The identification of small natural ligands that could prevent the entry and/or replication of the coronavirus remains a pertinent approach to fight the coronavirus disease (COVID-19) pandemic. Previously, we showed that the phenolic compounds corilagin and 1,3,6-tri-O-galloyl-β-D-glucose (TGG) inhibit the interaction between the SARS-CoV-2 spike protein receptor binding domain (RBD) and angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 108 publications
(144 reference statements)
1
25
0
Order By: Relevance
“…Further study indicated that tannic acid interfered with the binding of S-RBD to hACE2 in the clinical therapeutic dose range, and exhibited effective antiviral activity against pseudotyped SARS-CoV-2 entry. Molecular docking and molecular dynamic revealed that tannic acid could block S-RBD from binding to hACE2 by interacting with the essential residues of S-RBD-hACE2 interface, which is also in accordance with a recent research ( Haddad et al, 2022 ). Moreover, it is known that the SARS-CoV-2 spike glycoprotein is broadly mutated, with approximately 90% of the sequence being changed ( Bhattacharya et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Further study indicated that tannic acid interfered with the binding of S-RBD to hACE2 in the clinical therapeutic dose range, and exhibited effective antiviral activity against pseudotyped SARS-CoV-2 entry. Molecular docking and molecular dynamic revealed that tannic acid could block S-RBD from binding to hACE2 by interacting with the essential residues of S-RBD-hACE2 interface, which is also in accordance with a recent research ( Haddad et al, 2022 ). Moreover, it is known that the SARS-CoV-2 spike glycoprotein is broadly mutated, with approximately 90% of the sequence being changed ( Bhattacharya et al, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…The effectiveness of B. abyssinica water extract could be due high phenolic compounds that have been revealed by other studies to possess high antiviral activity [ 33 , 34 ]. The presence of tannins in stem bark extracts seems to have antiviral activity on coronavirus [ 35 , 36 ] where similar studies revealed similar activity of tannic acid on SARS-CoV-2 [ 37 ]. High amount of flavonoids were also revealed leaves extract of B. abyssinica which has been reported by several studies to have activity against SARS-CoV-2 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several compounds found in natural plants and food, such as tannin [ 26 ] and tannic acid [ 27 , 28 ], have been reported to have anti-SARS-CoV-2 effects in vivo and in vitro , respectively. Therefore, food-derived compounds with anti-SARS-CoV-2 effects, including those found in our current study, are expected to be useful for prevention and treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%